2007
DOI: 10.1016/j.molcel.2007.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Interaction of the Ribosome with the Switch Regions of GTP-Bound Elongation Factors

Abstract: Elongation factor G (EF-G) catalyzes tRNA translocation on the ribosome. Here a cryo-EM reconstruction of the 70S*EF-G ribosomal complex at 7.3 A resolution and the crystal structure of EF-G-2*GTP, an EF-G homolog, at 2.2 A resolution are presented. EF-G-2*GTP is structurally distinct from previous EF-G structures, and in the context of the cryo-EM structure, the conformational changes are associated with ribosome binding and activation of the GTP binding pocket. The P loop and switch II approach A2660-A2662 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

30
237
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(267 citation statements)
references
References 53 publications
30
237
0
Order By: Relevance
“…At 7.2-Å resolution, the interactions can only be approximated, and thus the closest residues between TetM and the ribosome at the site of density fusion are listed. In general, the contacts are similar to those reported previously for other translational GTPases, such as EF-G (21,22), LepA (23), and, at the domain level, TetO (14), and are discussed in more detail in the SI Appendix.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…At 7.2-Å resolution, the interactions can only be approximated, and thus the closest residues between TetM and the ribosome at the site of density fusion are listed. In general, the contacts are similar to those reported previously for other translational GTPases, such as EF-G (21,22), LepA (23), and, at the domain level, TetO (14), and are discussed in more detail in the SI Appendix.…”
Section: Resultssupporting
confidence: 81%
“…A large additional density within the subunit interface was attributed to TetM (Fig. 1A), as expected from the similarity in location of TetO (14) and EF-G (20)(21)(22) on the ribosome. In the absence of a crystal structure of any RPP, a homology model for TetM was built on the basis of the high sequence similarity between TetM and EF-G (10).…”
Section: Resultssupporting
confidence: 66%
“…1 and Fig. S3), in agreement with conclusions based on the results of numerous other approaches (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). In some cases, multiconformer analysis may provide information about molecular motions that is not evident from TLS-derived B factor values alone.…”
Section: Resultssupporting
confidence: 88%
“…Besides the high sequence and structure similarities, trGTPases share the way of association with the large ribosomal subunit, close to the A-site. Biochemical and structural studies identified the sarcin-ricin loop (SRL) of 23S rRNA as one of the most pivotal rRNA elements for trGTPase functioning (8)(9)(10)(11)(12). The SRL represents one of the most highly conserved sequences of ribosomal RNA, and its tip has been shown to closely approach the bound GTP molecule in the respective G domains of trGTPases (9,12).…”
mentioning
confidence: 99%